[tex]( \sqrt{5\sqrt{2} -1} -\sqrt{5\sqrt{2} +1 } )^{2} =(\sqrt{5\sqrt{2} -1}) ^{2} -2\cdot (\sqrt{5\sqrt{2} -1})\cdot (\sqrt{5\sqrt{2} +1})+( \sqrt{5\sqrt{2} 1} )^{2} =\mid 5\sqrt{2} -1}\mid -2\cdot ( \sqrt{(5\sqrt{2} -1)\cdot (5\sqrt{2} +1)}) +\mid 5\sqrt{2} +1}\mid =5\sqrt{2} -1-2\cdot \sqrt{(5\sqrt{2} )^{2} -1^{2} } +5\sqrt{2} +1=10\sqrt{2} -2\cdot \sqrt{50-1}=10\sqrt{2} -2\cdot \sqrt{49}=10\sqrt{2} -2\cdot \sqrt{7^{2} }=10\sqrt{2} -2\cdot 7=10\sqrt{7} -14[/tex]
I 5√2 - 1 I = 5√2 - 1 - opuszczam wartość bezwzględną bez zmiany znaku ponieważ : 5√2 - 1 > 0
I 5√2 + 1 I = 5√2 + 1 - opuszczam wartość bezwzględną bez zmiany znaku ponieważ : 5√2 + 1 > 0
Korzystam ze wzorów :
[tex](x-y)^{2} =x^{2} -2xy+y^{2} \\\\x^{2} -y^{2} =(x-y)\cdot (x+y)\\\\\sqrt{x^{2} } =\mid x \mid[/tex]
Odp: C. 10√7 - 14